PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI BUDAYA LOKAL KERINCI - Fidia, Dilla; Rusliah, Nur; Anggraini, Reri Seprina (Universitas Bhinneka PGRI, 2024)
This research aims to determine the increase in mathematical problem-solving abilities through the Problem-Based Learning (PBL) model integrated with local Kerinci culture. The approach used in this research is quantitative using a pre-experimental type. The design used is called One Group Pretest-Posttest. The essay question test is the instrument used in this research. The data from this study was not normally distributed, so the Wilcoxon test was used for statistical analysis. The Wilcoxon Sign Rank Test findings show a significance level (2-tailed) of 0.000. This shows that there is an improvement between the before and after tests, the test aims to help students improve their mathematical problem-solving abilities through the Problem-Based Learning (PBL) learning model integrated with local Kerinci culture.